TRANSFORMASI DIGITAL PADA LEMBAGA KEUANGAN MIKRO SYARIAH: ANALISIS IMPLEMENTASI, TANTANGAN, DAN STRATEGI PENGEMBANGAN BMT DI INDONESIA - Riyan Damara Putra; Shalahudin Habibullah; Fatih Fuadi (NATUJA: Jurnal Ekonomi Syariah, 2025)
Digital transformation in Islamic microfinance institutions, particularly Baitul Maal wat Tamwil (BMT), has become a strategic approach to expanding digital financial inclusion while improving the operational efficiency of community-based financial institutions. This study aims to examine the implementation of digital transformation in Indonesian BMTs, identify key challenges, and formulate development strategies aligned with Islamic principles. A Systematic Literature Review (SLR) was employed by analyzing peer-reviewed journal articles, institutional reports, and policy publications issued between 2020 and 2025. The findings indicate that BMTs with adequate asset capacity and governance structures are more prepared to adopt digital technologies comprehensively, particularly in transaction services, financing processes, and financial reporting. Digitalization initiatives in selected BMTs have demonstrated measurable improvements in operational efficiency and service outreach. Nevertheless, most BMTs remain at basic to intermediate stages of digital adoption due to infrastructure constraints, limited digital literacy among human resources, and regulatory complexity. This study emphasizes that BMT digital transformation should be implemented gradually, contextually, and in accordance with Islamic values, supported by collaboration with the Islamic fintech ecosystem and regulatory policy frameworks.